Maximality on Construction of Ternary Cross Bifix Free Code - Mohammad Affaf (Bina Nusantara University, 2019)
The purpose of this research was to show that ternary cross bifix free code CBFS3(2m+1) and CBFS3(2m+2) achieved the maximum for every natural number m. This research was a literature review. A cross bifix free codes was constructed by using Dyck path method which achieved the maximality, that was non-expandable on binary set sequences for appropriate length. This result is obtained by partitioning members of CBFS3(2m+1) and CBFS3(2m+2) and comparing them with the maximality of CBFS2(2m+1) and CBFS2(2m+2). For small length 3, the result also shows that the code CBFS3(3) is optimal.